‘Hanging in Imbalance’: Forensic Mental Health at Crossroads in Pakistan - Rana, Mowadat Hussain; Rana, Roop Zainab (Journal of Pakistan Psychiatric Society, 2020)
Four mentally ill individuals convicted of murder and sentenced to death, await their fate as the Supreme Court of Pakistan hears their appeals. After being declared patients of psychosis, their appeals at suspension of their execution were rejected at all judicial levels, and the sentence to hang them till death has been upheld so far in each case. Appeals challenging the legal validity of hanging a person suffering from mental illness are filed and the Supreme Court of Pakistan has formed a bench of five learned judges to decide on the matter. The outcome will have historical and far reaching futuristic legal and mental health policy implications. As of today, the issue hangs in balance, and can go either way.